Proceedings of the 57th Annual Meeting of the Association for Computational Linguistics 2019
DOI: 10.18653/v1/p19-1027
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Tagging with Contextual and Non-Contextual Subword Representations: A Multilingual Evaluation

Abstract: Pretrained contextual and non-contextual subword embeddings have become available in over 250 languages, allowing massively multilingual NLP. However, while there is no dearth of pretrained embeddings, the distinct lack of systematic evaluations makes it difficult for practitioners to choose between them. In this work, we conduct an extensive evaluation comparing non-contextual subword embeddings, namely FastText and BPEmb, and a contextual representation method, namely BERT, on multilingual named entity recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…When task-specific supervision is limited, e.g. sequence labeling in low resource languages, mBERT performs better than fastText while underperforming a single BPEmb trained on all languages (Heinzerling and Strube, 2019). Contrary to this work, we focus on mBERT from the perspective of representation learning for each language in terms of monolingual corpora resources and analyze how to improve BERT for low resource languages.…”
Section: Representations For Low Resource Languagesmentioning
confidence: 99%
“…When task-specific supervision is limited, e.g. sequence labeling in low resource languages, mBERT performs better than fastText while underperforming a single BPEmb trained on all languages (Heinzerling and Strube, 2019). Contrary to this work, we focus on mBERT from the perspective of representation learning for each language in terms of monolingual corpora resources and analyze how to improve BERT for low resource languages.…”
Section: Representations For Low Resource Languagesmentioning
confidence: 99%
“…This is the baseline setting. We also compare our results to multilingual embeddings (Multi) which have been successfully used in monolingual settings as well (Heinzerling and Strube, 2019). To ensure comparability, we use the multilingual versions of BPEmb and FLAIR, which were trained simultaneously on 275 and 300 languages, respectively.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Furthermore, [79] found that although mBERT performs well in scenarios with medium and high language resources, non-contextual embedding working at the sub-word level, such as BPEmb, outperforms mBERT in low-resources scenarios. Finally, [80] explored cross-lingual transfer for Danish using several architectures for supervised NER, including Flair, fastText, BPE and both monolingual (Danish) and multilingual BERT, on a modestly-sized training set, testing different training and fine-tuning approaches.…”
Section: Background and Related Workmentioning
confidence: 99%